2020
DOI: 10.1186/s12987-020-00232-1
|View full text |Cite
|
Sign up to set email alerts
|

Water treadmill training attenuates blood-spinal cord barrier disruption in rats by promoting angiogenesis and inhibiting matrix metalloproteinase-2/9 expression following spinal cord injury

Abstract: Background The permeability of the blood-spinal cord barrier (BSCB) is mainly determined by junction complexes between adjacent endothelial cells (ECs), including tight junctions (TJs) and adherens junctions (AJs), which can be severely damaged after spinal cord injury (SCI). Exercise training is a recognized method for the treatment of SCI. The destruction of the BSCB mediated by matrix metalloproteinases (MMPs) leads to inflammation, neurotoxin production, and neuronal apoptosis. The failure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…It has also been reported that rehabilitative training can promote axonal regeneration in peripheral nerve injury [ 21 ], but the specific mechanism by which rehabilitative training affects axonal outgrowth in the CNS has not been determined. In this study, we combined a treadmill with swimming (to avoid potential injuries caused by early intensive training) and used the water treadmill [ 22 ] to explore the mechanism underlying neurite outgrowth after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that rehabilitative training can promote axonal regeneration in peripheral nerve injury [ 21 ], but the specific mechanism by which rehabilitative training affects axonal outgrowth in the CNS has not been determined. In this study, we combined a treadmill with swimming (to avoid potential injuries caused by early intensive training) and used the water treadmill [ 22 ] to explore the mechanism underlying neurite outgrowth after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Locomotor training combined with epidural stimulation, moreover, increases capillary distribution across the muscle after SCI (Kissane et al, 2019). Recently, researchers have found that water treadmill training (TT) reduces BSCB permeability after SCI by inhibiting MMP-2/9 expression (Ying et al, 2020). TT also triggers the BDNF/TrkB-CREB signaling pathway to ameliorate BSCB disruption following SCI (Ying et al, 2021).…”
Section: Physical Stimulationmentioning
confidence: 99%
“…Fibrin (Yao et al, 2018a;Loureiro et al, 2019), HA (Wei et al, 2010), Collagen (Wang et al, 2018) Synthetic materials PLL (Patist et al, 2004), PLGA (Yu et al, 2016b;Ropper et al, 2017) Physical stimulation CMH (Halder et al, 2018), Training (Kissane et al, 2019;Ying et al, 2020Ying et al, , 2021, tsDCS (Samaddar et al, 2017) (tsDCS) promotes blood flow to modulate neural cell migration and proliferation after SCI (Samaddar et al, 2017).…”
Section: Natural Materialsmentioning
confidence: 99%
“…VEGF promotes endothelial cell proliferation, vascularization, and angiogenesis, and is upregulated by exercise via lactate receptors expressed in the blood–brain barrier [ 172 ]. After SCI, the exercise-induced increase in VEGF is associated with enhanced expression of tight junctions and adherens junctions, which reduces blood–spinal-cord barrier permeability and improves locomotor recovery [ 173 ]. This effect was further shown to rely on BDNF/TrkB signaling [ 47 ], as well as inhibition of matrix metalloproteinases (MMPs) [ 173 ], which restructure extracellular matrices and damage the blood–spinal-cord barrier after SCI [ 174 , 175 ].…”
Section: Other Considerationsmentioning
confidence: 99%
“…After SCI, the exercise-induced increase in VEGF is associated with enhanced expression of tight junctions and adherens junctions, which reduces blood–spinal-cord barrier permeability and improves locomotor recovery [ 173 ]. This effect was further shown to rely on BDNF/TrkB signaling [ 47 ], as well as inhibition of matrix metalloproteinases (MMPs) [ 173 ], which restructure extracellular matrices and damage the blood–spinal-cord barrier after SCI [ 174 , 175 ]. Interestingly, another study found that after SCI, proliferating endothelial cells located in the core of the lesion upregulate CD200, which hinders inflammation [ 176 ], while yet another study found that treadmill exercise upregulates both CD200 and its receptor after stroke in rats [ 177 ].…”
Section: Other Considerationsmentioning
confidence: 99%